2013
DOI: 10.1097/tp.0b013e31829434d4
|View full text |Cite
|
Sign up to set email alerts
|

Early Versus Late Acute Antibody-Mediated Rejection in Renal Transplant Recipients

Abstract: Compared with early aABMR, late aABMR had inferior graft survival and was characterized by young age, frequent nonadherence, or suboptimal immunosuppression and de novo donor-specific antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 50 publications
6
65
1
1
Order By: Relevance
“…Similar complications were described after treatment of AMR in kidney transplant recipients. 6 Immunosuppressive treatment of AMR is based on antibody removal and therapy to suppress further synthesis; it is challenging, and no consensus guidelines exist. As emphasized by a recent survey, the treatment of AMR is heterogeneous across hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar complications were described after treatment of AMR in kidney transplant recipients. 6 Immunosuppressive treatment of AMR is based on antibody removal and therapy to suppress further synthesis; it is challenging, and no consensus guidelines exist. As emphasized by a recent survey, the treatment of AMR is heterogeneous across hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Late AMR may be associated with a worse prognosis compared with early AMR. 6,7 However, little is known concerning late AMR after heart transplantation. In a previous cohort of 15 patients, Hodges et al 4 showed that late AMR was associated with poor short-term prognosis despite aggressive immunosuppressive therapies.…”
mentioning
confidence: 99%
“…Late AMR is associated with chronic pathology and worse dysfunction at the time of diagnosis, mixed cellular and humoral features, and subsequently, lower treatment response rates, [132][133][134] but it is notable that DSA MFI does not reliably further stratify those individuals who will respond to treatment from those who will do not. 133 Indeed, in one study, those who responded to treatment had higher antibody level as estimated by MFI than nonresponders.…”
Section: Dndsa and Features Of Amrmentioning
confidence: 99%
“…Однако важнейшим фактором, определяющим клиническую картину и течение отторжения, является комплаентность па-циента и адекватность иммуносупрессивной тера-пии в целом. Так, по данным Dörje с соавторами, клинически манифестные формы острого гумо-рального отторжения были ассоциированы имен-но с этими факторами [27]. В нашем исследовании преобладали случаи вялотекущего/субклиническо-го течения ОГО, и значительно чаще процесс выяв-лялся на стадии ХОТ (39 vs 85 пациентов).…”
Section: Discussionunclassified